2020
DOI: 10.2991/dsahmj.k.200206.002
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Lebanese Pharmacists towards the Use and Misuse of Gabapentinoids and Tramadol: A Cross-sectional Survey

Abstract: Community pharmacists are the most accessible healthcare professionals. Recently, the increasing trend of tramadol and gabapentinoids prescription has become a global problem, with a high risk of misuse and abuse. This study mainly assessed the knowledge and practice of Lebanese pharmacists regarding the use of gabapentinoids and tramadol, and also identified the predictors of knowledge. A cross-sectional survey was conducted on a sample of 295 Lebanese community pharmacists over a period of 4 months. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, acknowledging their inherent risks, weak opioids such as codeine and tramadol were classified as controlled drugs and cannot be dispensed by pharmacists without a doctor’s prescription, including dentists. 25 , 26 Despite this restriction in Lebanon, local data from a pharmacist’s perspective expressed the need for better supervision on sales and better governmental regulations to limit possible misuse or abuse. 26 In addition to opioids, clinicians should acknowledge the toxicity of NSAIDs and their potential interactions and adverse effects, especially that, in Lebanon, these medications are available over-the-counter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, acknowledging their inherent risks, weak opioids such as codeine and tramadol were classified as controlled drugs and cannot be dispensed by pharmacists without a doctor’s prescription, including dentists. 25 , 26 Despite this restriction in Lebanon, local data from a pharmacist’s perspective expressed the need for better supervision on sales and better governmental regulations to limit possible misuse or abuse. 26 In addition to opioids, clinicians should acknowledge the toxicity of NSAIDs and their potential interactions and adverse effects, especially that, in Lebanon, these medications are available over-the-counter.…”
Section: Discussionmentioning
confidence: 99%
“…25 , 26 Despite this restriction in Lebanon, local data from a pharmacist’s perspective expressed the need for better supervision on sales and better governmental regulations to limit possible misuse or abuse. 26 In addition to opioids, clinicians should acknowledge the toxicity of NSAIDs and their potential interactions and adverse effects, especially that, in Lebanon, these medications are available over-the-counter. Therefore, dentists should advise their patients to avoid self-medication and should be extremely cautious when prescribing this class of analgesics in older patients, in patients with gastrointestinal problems, or taking aspirin, oral anticoagulants (vitamin K antagonists), or corticosteroids, due to the risk of gastric bleeding and peptic ulcer disease.…”
Section: Discussionmentioning
confidence: 99%
“…No previous study has been conducted on community pharmacists' perceptions towards pregabalin misuse and abuse in Saudi Arabia; therefore, the survey was adopted from four previous studies conducted elsewhere [3,23,24,28]. The questionnaire consisted of 21 questions on 2 domains; Domain I: 10 questions related to demographics; Domain II: 11 questions on perception with open and closed questions related to community pharmacists' perceptions towards pregabalin misuse and abuse.…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted in Jordan on community pharmacist's experiences of pregabalin misuse and abuse among their customers reveals that most participants (87.4%) reported cases of pregabalin abuse in their pharmacies [23]. Another study conducted in Lebanon reported that pharmacists might need to improve their knowledge concerning tramadol and gabapentinoids (α 2 δ ligands) [24]. Pregabalin was deemed a safe and effective medication for pain and helping with sleep in a Chinese study area at doses of 300-450 mg per day [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, while the Ministry of Public Health continually inspects tramadol dispense records, no clear regulations to control gabapentinoids dispensing. That is, the latter may be dispensed by pharmacists without a prescription [13].…”
Section: Methodsmentioning
confidence: 99%